2020
DOI: 10.1002/ptr.6702
|View full text |Cite
|
Sign up to set email alerts
|

Fruits ofTerminalia chebulaRetz.: A review on traditional uses, bioactive chemical constituents and pharmacological activities

Abstract: Fruits of Terminalia chebula Retz. (Combretaceae) are widely used as crude drugs in various traditional medicine systems. The aim of this article is to review the available scientific information regarding the traditional uses, bioactive chemical constituents and the pharmacological activities of T. chebula. Numerous researches conducted on T. chebula have confirmed the presence of wide range of the phytochemicals such as flavonoids, tannins, phenolic acids and other bioactive compounds. T. chebula is also wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 98 publications
0
52
0
Order By: Relevance
“…Fruit contains protein (3.78%), carbohydrate (9.21%), and vitamin C (369 ppm), starch (1.22%), sucrose (3.74%), reducing sugars (7.56%), and reducing substances (11.5%). The weight of hareer fruit pulp is 2.99 g, fruit peel 0.40 g, and pit weight 1.51 g (Nigam et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fruit contains protein (3.78%), carbohydrate (9.21%), and vitamin C (369 ppm), starch (1.22%), sucrose (3.74%), reducing sugars (7.56%), and reducing substances (11.5%). The weight of hareer fruit pulp is 2.99 g, fruit peel 0.40 g, and pit weight 1.51 g (Nigam et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, T. chebula has many pharmacological activities such as antiviral, antioxidant, antibacterial, antifungal, anti-protozoal, anti-carcinogenic, anti-mutagenic, radio-protective, chemo-preventive, hepato-protective, cardio-protective, cyto-protective, anti-diabetic, reno-protective, anti-inflammatory, anti-arthritic, adaptogenic, anti-anaphylactic, hypolipidemic, hypocholesterolemic, anti-caries, wound healing, anti-allergic, immunomodulatory, anti-ulcer, anti-spasmodic and gastrointestinal motility properties [ 232 , 233 , 235 , 236 , 237 ]. Lin et al, 2013 conducted an in vitro study and found that chebulagic acid and punicalagin from the fruit of T. chebula have the potential to inhibit the activity of different viruses, such as human cytomegalovirus, HCV, dengue virus, measles virus, and respiratory syncytial virus [ 234 ]. Due to its strong biological properties, it is highly recommended to study T. chebula as a possible remedy against SARS-CoV-2.…”
Section: Other Medicinal Plants In Use Against Various Viral Infecmentioning
confidence: 99%
“…Considering a large number of medicinal plant species identified that would be very extensive to analyze, reference will be made only to species with a high and medium level of use in formulations (Table 1). The results suggested that 100% of the reported plant species, far from being of exclusive veterinary use, were extensively used in humans (Bijak, 2017;Dewangan et al, 2020;Fourati et al, 2020;Gucwa et al, 2018;Hossain & Mizanur Rahman, 2019;Javir & Joshi, 2019;Lu et al, 2019;Ma et al, 2020;Murugan et al, 2020;Nigam et al, 2020;Rose et al, 2019;Singh et al, 2019;Sabir et al, 2020;Saggam et al, 2020;Santhan, 2020;Saha et al, 2020;Singh & Geetanjali, 2016;Yadav et al, 2020;Yu et al, 2020;Zhang et al, 2020). The pronounced convergence found evinces the similarities between ethnomedical and ethnoveterinary knowledge (Miara et al, 2019) and reinforces the "one health, one medicine" concept.…”
Section: Resultsmentioning
confidence: 75%